2017
DOI: 10.1021/acs.energyfuels.7b02507
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Representation of Petroleum Residues Using Fourier Transform Ion Cyclotron Resonance Mass Spectrometry and Conventional Analysis

Abstract: A methodology for structurally representing the molecules of three Colombian vacuum residues (538+ °C) and one Mexican atmospheric residue (300+ °C) is reported. Information obtained by Fourier transform ion cyclotron resonance mass spectrometry coupled to positive electrospray ionization, negative electrospray ionization, and positive atmospheric pressure photoionization sources and conventional standardized analytical methods was used for molecular representation of the samples. The generation of molecules w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…This is even more remarkable, as saturates are determined indirectly by the mass spectrometric method, i.e., as balance to the aromatic compounds. Obviously, the described simplifications pertaining to equal aromatic compound response factors misrepresent a known APPI bias against low DBE species described earlier . Diaromatic compounds are overestimated in all samples, while triaromatic compounds seem underrepresented.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…This is even more remarkable, as saturates are determined indirectly by the mass spectrometric method, i.e., as balance to the aromatic compounds. Obviously, the described simplifications pertaining to equal aromatic compound response factors misrepresent a known APPI bias against low DBE species described earlier . Diaromatic compounds are overestimated in all samples, while triaromatic compounds seem underrepresented.…”
Section: Resultsmentioning
confidence: 88%
“…One approach for heavy ends characterization is based on creating a quantitative description (a compositional model) of the sample. Various mathematical functions represent molecular property distributions and are optimized to fit various bulk and speciation measurements. The combination of several analytical speciation techniques, including multidimensional fractionation by liquid chromatography followed by high-resolution mass spectrometry with multiple modes of ionization (field desorption/field ionization FD/FI, APPI, ESI positive and negative modes), has also been described to build a compositional model . Inevitably, model reconciliation is needed through adjustment of component distributions such as heteroatom classes, ring numbers, carbon numbers, etc., until the sample’s physical and chemical properties, like boiling point distribution, elemental analysis, and/or density, are matched. …”
Section: Introductionmentioning
confidence: 99%
“…This fraction is known as vacuum residue (VR), and is characterised by its high complexity and heteroatomic content (N, S, O and traces of metals). While FT-ICR MS is well-known to be an extremely versatile technique, uniquely suited to the detailed molecular characterization of complex samples,26,27,60 it has been demonstrated that a more complete characterization of the composition of heavy ends of petroleum can be afforded by the prior separation or fractionation of the sample 61. Due to the low volatility of the components of vacuum residues, however, they cannot be chromatographically separated: they are not amenable to gas chromatography (GC)62,63 or liquid chromatography (LC) 64.…”
Section: Resultsmentioning
confidence: 99%
“…To date, Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR MS) has represented the state-of-the-art, offering the highest performance in terms of both resolving power and mass accuracy4,5 and providing abilities to resolve components of complex mixtures without any prior fractionation and to assign molecular formulae with sub-ppm mass accuracy. This has been demonstrated with respect to applications such as natural organic matter,611 metabolomics,1214 proteomics,15,16 and petroleum-related samples, now known as petroleomics,1727 amongst others. Whilst significant progress has been made in these fields, challenges remain.…”
Section: Introductionmentioning
confidence: 99%
“…Petroleum is one of the most complex mixtures found in nature and can contain hundreds of thousands of unique elemental compositions within a single sample . The study of petroleum composition has become known as “petroleomics”. Developing a more detailed understanding of petroleum composition in order to address the challenges of producing and refining crude oil has become increasingly important in recent years. Fourier transform ion cyclotron resonance mass spectrometry (FTICR MS) is a state-of-the-art technique for petroleomics that provides a significant ultrahigh resolving power and mass accuracy to assign elemental compositions of highly complex samples . FTICR cells can hold a maximum of a few million ions, and singly charged ions will be detected if their presence reaches the detectable amount of at least 50 to 100 ions. , If several thousands of molecular compositions are present, many species can fall below the detection limit .…”
mentioning
confidence: 99%